2016
DOI: 10.1371/journal.pone.0147508
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Dialysis Visits to a Nephrology Department and Major Cardiovascular Events in Patients Undergoing Dialysis

Abstract: Background and ObjectivesPre-dialysis care by a nephrology out-patient department (OPD) may affect the outcomes of patients who ultimately undergo maintenance dialysis. This study examined the effect of pre-dialysis care by a nephrology OPD on the incidence of one-year major cardiovascular events after initiation of dialysis.Design, Setting Participants, & MeasurementsThe study consisted of Taiwanese patients with chronic kidney disease (CKD) who commenced dialysis from 2006 to 2008. The number of nephrology O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Nephrological monitoring of CKD patients is recommended by clinical guidelines starting at CKD stage 3b [ 25 ] or later [ 23 ]. Besides improved survival, numerous additional advantages have been described, such as better cardiovascular morbidity [ 32 ] and, in line with the findings of the current study, better control of anemia and nutritional status [ 7 , 33 ] and a higher frequency of dialysis initiation via an AVF [ 34 ]. While a causative analysis of specific aspects of predialysis nephrological care on improved long-term morbidity and mortality after dialysis initiation is beyond the scope of this article, these findings may be indicative of the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 70%
“…Nephrological monitoring of CKD patients is recommended by clinical guidelines starting at CKD stage 3b [ 25 ] or later [ 23 ]. Besides improved survival, numerous additional advantages have been described, such as better cardiovascular morbidity [ 32 ] and, in line with the findings of the current study, better control of anemia and nutritional status [ 7 , 33 ] and a higher frequency of dialysis initiation via an AVF [ 34 ]. While a causative analysis of specific aspects of predialysis nephrological care on improved long-term morbidity and mortality after dialysis initiation is beyond the scope of this article, these findings may be indicative of the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 70%
“…Based on the observations about time to dialysis, eGFR value, and access at dialysis initiation, our chart review suggests that Chinese American patients at Tufts Medical Center received care equivalent to other participants. Literature suggests that patients with more pre-dialysis visits had better peritoneal dialysis-related outcomes, fewer cardiovascular events and lower mortality [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported on the prevalence of nephrology care among patients with CKD. [23,24,25] Huang et al [23] reported that 77.1% of patients who initiated dialysis from 2006 to 2008 had at least 1 nephrology-related visit during the previous 3 years. However, nephrology visit rates are usually quite low among patients with an eGFR of <60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%